“Fighting spirit”: specific personality traits as one of the key factors for sport championship in type 1 diabetes mellitus - Cyranka, Katarzyna (Diabetol Int, 2021)
There is ample evidence that sport is a protective factor against a number of health risks, across all ages, in the general population. An in-depth understanding of energy metabolism has reasonably entailed exercise as a cornerstone in the lifestyle of almost all subjects with type 1 diabetes mellitus (T1DM). Nevertheless, individuals with T1DM often fail in accomplishing exercise guidelines and they are often less active than their peer without diabetes. Two major obstacles are feared: management of blood glucose control and hypoglycemia. Nowadays, strategies, including glucose monitoring technology and insulin pump therapy, have significantly contributed to the participation in regular physical activity, and even in competitive sports, for T1DM people. The case report presents an analysis of specific personality traits and psychological parameters of 20 years old female Polish multiple champion in weightlifting with excellent T1DM control.